Comparison of Applications of Aloe Vera, Honey, Saliva, and Ovalbumin on Collagen Formation in Wound Healing of Incised Skin in Rats - R. Wahyu Kartiko Tomo; Ishandono Dachlan; Dewajani Dewajani (Academic Hospital Journal, 2018)
Background: Aloe vera, honey, human saliva, and ovalbumin are useful in the wound healing process. Collagen acts as an indicator of wound healing.Objective: This research aimed to compare the effect of Aloe vera, honey, human saliva and ovalbumin on collagen formation in wound healing.Design: This research was a laboratory experimental study on sixty white rats (Rattus novergicus) which were divided into 5 groups. Four groups were cases with skin applications and 1 group was controls with NaCl. We performed general anesthesia procedure, making an incision on skin of back, then the wound was sutured, and on surface of the sutured wound we applied substrate twice a day for six days. On day four and seven, after euthanasia, the sutures were removed, and the incised skin was taken for histological examination. We counted and analyzed the size of collagen with Image Raster tool programs. Data were analyzed with t-test, Mann Whitney, ANOVA and Kruskal Wallis tests, and then with post hoc tests.Results: After day four, the mean area of collagen of Aloe vera group was 55391.19 ± 30939.63, honey 24194.88 ± 43700.39, saliva 25869.86 ± 31608.39, ovalbumin 82459.19 ± 80994.66, NaCl  97658.04 ± 88452.74, with no significant differences between collagen sizes with p=0.125 (˃0.05). Decapitation day seven, significant differences with p=0.017 (˂0.05), in honey group 18601.67 ± 29260.28 and saliva 17560.31 ± 27262.03 than the control NaCl  94126.22 ± 29500.27.Conclusions: Collagen sizes after day four among the groups of Aloe vera, honey, saliva, ovalbumin and saline did not differ significantly. Collagen sizes after day seven of honey and saliva groups were significantly different than the controls.